Management of children with acute pancreatitis: An intensivist perspective - Maninder Singh Dhaliwal; Veena Raghunathan; Deepak Goyal; Shaun Siong Chung Ho (Wolters Kluwer Medknow Publications, 2016)
The incidence of acute pancreatitis (AP) in children is slowly increasing. Etiological pattern of AP in children is varied and unlike adults; it mainly includes trauma, infection, medications and idiopathic causes. AP is characterised by severe abdominal pain, 3 fold elevation in amylase and/or lipase & characteristic findings on imaging. Early diagnosis is essential for appropriate management; however this is challenging especially in young and sick children where symptoms may not be forthcoming. Also overlapping symptoms and laboratory investigations in certain scenarios such as diabetic ketoacidosis and head trauma may lead to diagnostic difficulties. Regardless of etiology, the evolution of AP has 2 common phases which need to be recognised by the intensivist. These include initial phase of SIRS and subsequent phase of infectious complications; both of which can be potentially lethal. Clinical severity scoring systems used in adults are not applicable to children with AP. 7 fold rise in serum lipase appears to be an accurate predictor of severity in children. Essential to management is early aggressive fluid resuscitation (within 6-12 hours of admission) which should be guided by monitoring of various hemodynamic parameters in PICU rather than fixed fluid guidelines. Intravenous contrast enhanced CT of the abdomen is required to assess the severity of AP and extent of regional complications. It is however best delayed until hemodynamic stabilisation or for at least 48-72 hours after onset of symptoms. Pain management and early nutrition are important aspects of care along with close monitoring for development of multi-organ dysfunction. This review attempts to address AP in children from a pediatric intensivist's perspective.